A Comparative Study between Three-Legged and Tripod Sub-structures in Design of Offshore Wind Turbines in the Transition Water Depth - Khosravi, Aliakbar; Wai Yeong, Tuck; Parvez Anwar, Mohammed; Jaganathana, Jayaprakash; Leong Lau, Teck; Elleithy, Wael (International Journal of Engineering and Technology, 2018)
This research aimed at investigating tripod and three-legged offshore wind turbine substructures. A comparison between the two substructures based on their weight as well as the installation method of piles, i.e. pre-piling and post-piling, was carried out. The in-place (Ultimate Limit State), Dynamic, natural frequency check and fatigue (Fatigue Limit State) analyses were conducted considering aerodynamic and hydrodynamic loads imposed on substructures in 50m water depth. An optimisation process was carried out in order to reduce the mass of substructures. The results revealed that the three-legged substructure is more cost effective with 25% lesser structure mass. However, the construction of the three-legged structure usually takes more time due to increased number of members and subsequently welding joints. The results, furthermore, showed that the pre-piling method reduces the time and cost of offshore installation, and reduces the weight of piles by 50%.Â Â